RESTRUKTURISASI SISTEM DAN OPTIMALISASI PROGRAM PEMBERDAYAAN MASYARAKAT MISKIN PADA SEKTOR MIKRO - Siti Murtiyani (Pusat Studi Ekonomi Islam Sekolah Tinggi Ekonomi Islam Hamfara, 2016)
Unemployment and poverty are major problems for a country, this study aims to provide solutions to optimize the performance of government agencies and related organizations, how this synergistic collaboration will be able to strengthen empowerment programs for the poor to be independent and sustainable with success in managing business units in real sector. The method used is to form groups of business units (clusters) in each business unit and mutually reinforcing between groups and networks (Networking) that are structured and strong. The program approach uses the Participatory Rural Appraisal (PRA) and Participatory Action Research (PAR) model, a centralized local approach (target group) in the mentoring process for its business units. The results of the research are in the form of an integrated system and strategies to strengthen synergistic and sustainable cooperation for the Government, Bank Indonesia, Islamic Banks, Educational Institutions and other social institutions such as BAZNAS, LAZIS, Dompet Dhuafa Republika and other social organizations, as well as providing recommendations so that each institution can synergize the program. work to be more structured and focused on empowerment programs for the poor.